Strategi Penurunan Non Revenue Water (NRW) di DMA Graha Permata Kota (GPK) PT Air Minum Giri Menang (Perseroda) - Jurmawanti, Jurmawanti; Soedjono, Eddy Setiadi; Hastuti, Dian Suci (Universitas Tanjungpura, 2025)
Water loss in clean water distribution systems includes both physical and non-physical losses, which affect service efficiency and financial performance. One of the key indicators of such losses is Non-Revenue Water (NRW), defined as water that is produced but does not generate revenue. The Graha Permata Kota District Metered Area (DMA GPK), managed by PT Air Minum Giri Menang (Perseroda), recorded the highest NRW level at 38.63%. This study aims to evaluate the condition of water loss in DMA GPK, identify its causes, and formulate mitigation strategies using water balance analysis and the SWOT (Strengths, Weaknesses, Opportunities, and Threats) approach. Primary data were collected from 24-hour monitoring of pressure and flow, while secondary data included pipeline maps, inlet volumes, and operational records from January 2024 to March 2025. The analysis revealed that most losses were due to physical leakage in aging PVC pipelines. DMA GPK falls under SWOT Quadrant II (Weaknesses